A New Player at the Flagellar Motor: FliL Controls both Motor Output and Bias - Jonathan D. Partridge (American Society for Microbiology, 2015)
ABSTRACT The bacterial flagellum is driven by a bidirectional rotary motor, which propels bacteria to swim through liquids or swarm over surfaces. While the functions of the major structural and regulatory components of the flagellum are known, the function of the well-conserved FliL protein is not. In Salmonella and Escherichia coli, the absence of FliL leads to a small defect in swimming but complete elimination of swarming. Here, we tracked single motors of these bacteria and found that absence of FliL decreases their speed as well as switching frequency. We demonstrate that FliL interacts strongly with itself, with the MS ring protein FliF, and with the stator proteins MotA and MotB and weakly with the rotor switch protein FliG. These and other experiments show that FliL increases motor output either by recruiting or stabilizing the stators or by increasing their efficiency and contributes additionally to torque generation at higher motor loads. The increased torque enabled by FliL explains why this protein is essential for swarming on an agar surface expected to offer increased resistance to bacterial movement. IMPORTANCE FliL is a well-conserved bacterial flagellar protein whose absence leads to a variety of motility defects, ranging from moderate to complete inhibition of swimming in some bacterial species, inhibition of swarming in others, structural defects that break the flagellar rod during swarming in E. coli and Salmonella, and failure to eject the flagellar filament during the developmental transition of a swimmer to a stalk cell in Caulobacter crescentus. Despite these many phenotypes, a specific function for FliL has remained elusive. Here, we established a central role for FliL at the Salmonella and E. coli motors, where it interacts with both rotor and stator proteins, increases motor output, and contributes to the normal rotational bias of the motor.